COVID-19 AND LABOR MIGRATION OF NEED, DESPAIR, POVERTY FROM UKRAINE TO EUROPE - Koshulko, Oksana; Dzholos, Sergii (MEST Journal, 2021)
The article presents the results of research concerning the current issues of Ukrainian labor migrants to Poland and other European countries before and during the pandemic, as well as results of the analysis of the actions of the current Ukrainian Government’s attempts to stop migration flows from Ukraine. Primary and secondary sources of information have been used in the process of preparing the article. Primary data was collected using qualitative case studies conducted among labor migrants in Poland and Ukraine from 2018 to 2020. Secondary data was taken from Ukrainian, Polish, and other international sources of information. In particular, the secondary data of information was taken from open publications and open sources. Also, in the article, the four categories of need, which pushed Ukrainian labor migrants to work abroad, have been identified and characterized. Besides, an evaluation has been given of the Ukrainian Government’s performance, at the time when it was attempting to stop the migration flows from Ukraine to other countries of Europe but left no alternatives for its workers within the country. In general, analysis of challenges of Ukrainian labor migration to other countries of Europe during the international COVID-19 pandemic is a topical and timely subject for research.